Progress in the understanding of light‐ and elevated temperature‐induced degradation in silicon solar cells: A review. (17th November 2020) - Chen, Daniel; Vaqueiro Contreras, Michelle; Ciesla, Alison; Hamer, Phillip; Hallam, Brett; Abbott, Malcolm; Chan, Catherine
Abstract: At present, the commercially dominant and rapidly expanding PV‐device technology is based on the passivated emitter and rear cell (PERC) design developed at UNSW. However, this technology has been found to suffer from a carrier‐induced degradation commonly referred to as 'light‐ and elevated temperature‐induced degradation' (LeTID) and can result in up to 16% relative performance losses. LeTID was recently shown to occur in almost every type of silicon wafer, independent of the doping material. Even though the degradation mechanism is known to recover under normal operation conditions, it is a lengthy process that drastically affects the energy yield, stability and, ultimately, the levelized cost of electricity (LCOE) of installed systems. Despite the joint effort of many research groups, the root cause of the degradation is still unknown. Here, we provide an overview of the existing literature and describe key LeTID characteristics and how these have led to the development of various theories of the underlying mechanism. Further, given the continuously appearing and strong evidence of hydrogen involvement in LeTID, many mitigation methods concerning hydrogenation have been suggested. We discuss such reported methods, bearing in mind crucial consumer necessities in terms of sustained cell performance and minimised LCOE. Abstract : For many years, light‐ and elevated temperature‐induced degradation (LeTID) has captured the interest of researchers and manufacturers across the photovoltaic industry, who have raced to find solutions and elucidate its underlying cause. In this review, we bring together the collective findings and theories identified throughout the literature, providing a concise view of the current progress in understanding the defect. The review focuses upon the various unique properties and defect characteristics of LeTID, its degradation kinetics, root cause and mitigation strategies.